2021
DOI: 10.1002/edn3.206
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding as a tool to examine cryptic algae in the diets of two common grazing surgeonfishes, Acanthurustriostegus and A. nigrofuscus

Abstract: Surgeonfishes (Acanthuridae) are an important group of herbivores that are abundant on reefs globally. Acanthurids consume macroalgae that can compete with corals for space, turf algae that can proliferate on degraded reefs, and detritus that may smother adult corals or inhibit settlement. For these reasons, they are of particular interest at present to resource managers seeking to restore and conserve reefs that are facing a myriad of stressors. To contribute to our understanding of the diet breadth and poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…For example, highly diverse pomacentrid assemblages at Dongsha Atoll displayed a similar isotopic niche space to pomacentrids in Moorea (French Polynesia), despite much lower species richness in the latter (Gajdzik et al, 2018 ). Similarly, and contrary to expectations, surgeonfish with different morphologies have a similar dietary range (Brandl et al, 2015 ; Nalley, Donahue, & Toonen, 2022 ), suggesting species may differ across other axes of their trophic niches which are not reflected in the isotopic ratios (Schoener, 1974 ). It is clear from these examples, and our data, that only analyzing δ 15 N and δ 13 C misses important ecological information that could help explain unexpected niche overlaps.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, highly diverse pomacentrid assemblages at Dongsha Atoll displayed a similar isotopic niche space to pomacentrids in Moorea (French Polynesia), despite much lower species richness in the latter (Gajdzik et al, 2018 ). Similarly, and contrary to expectations, surgeonfish with different morphologies have a similar dietary range (Brandl et al, 2015 ; Nalley, Donahue, & Toonen, 2022 ), suggesting species may differ across other axes of their trophic niches which are not reflected in the isotopic ratios (Schoener, 1974 ). It is clear from these examples, and our data, that only analyzing δ 15 N and δ 13 C misses important ecological information that could help explain unexpected niche overlaps.…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that using a single tracer, such as only δ 15 N, δ 13 C, or δ 34 S, may hide important dietary variation, and lead to false conclusions regarding shared resources among groups. Multivariate analyses more accurately capture the extent of the isotopic niche space, representing a more comprehensive view of a species' trophic ecology, which is likely to be inherently variable (Nalley, Donahue, & Toonen, 2022 ; Skinner, Mill, et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acanthurus triostegus are common throughout coral reefs in the tropical Indo‐Pacific Ocean and it is a grazing reef herbivore that feeds primarily on filamentous algae and cylindrical algae, as well as some cyanobacteria, foliose algae, and calcareous algae (Nalley et al, 2021; Randall, 1961). Metabarcoding of diet contents of A. triostegus in Hawai'i identified 64 unique diet items, with Rhodophyta dominating the abundance, followed by ochrophyta and cyanobacteria (Kelly et al, 2016; Nalley et al, 2021). These abundant coral reef fish exhibit both shoaling and solitary behavior on both islands (Guerra et al, 2022), providing an excellent opportunity to explore the ecology of shoaling behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Most eDNA studies focus on metabarcoding of animals or land plants (Deiner et al, 2017), while only a few studies have explored the use of eDNA to track the export of macroalgae to the open ocean (Ortega et al, 2019) or the contribution of marine plants and macroalgae to sediment pools or food webs, with various success (del Carmen Gomez Cabrera et al, 2019; Nalley et al, 2021; Ortega et al, 2020; Queirós et al, 2019; Reef et al, 2017). The use of eDNA combined with sediment chronologies would also enable the identification of community changes over time (Bálint et al, 2018), as demonstrated by documented invasion of seagrass species in the Eastern Mediterranean (Wesselmann et al, 2021) and community changes in coral reefs of Australia (del Carmen Gomez Cabrera et al, 2019).…”
Section: Introductionmentioning
confidence: 99%